2018
DOI: 10.1590/1678-992x-2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

Biochar versus hydrochar as growth media constituents for ornamental plant cultivation

Abstract: Biochar and hydrochar have been proposed as novel materials for providing soilless growth media. However, much more knowledge is required before reliable advice can be given on the use of these materials for this purpose. Depending on the material and the technology applied (pyrolysis or hydrothermal carbonization), phytotoxicity and greenhouse gas emissions have been found for certain chars. In this study, our aim was to assess the feasibility of three chars as substrate constituents. We compared two biochars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In addition to production conditions, biochars could be made from varying feedstocks, which would contribute to differences in physical and chemical properties ( Table 1). The feedstocks could be waste materials such as green waste [18], forest waste [46,47], wheat straw [5], sugarcane bagasse [48], rice hull [49], crab shell [50] and Eucalyptus saligna wood chips (byproduct of construction, fuel-wood and pulp wood) [51]. Biochars could also be made from non-waste materials such as holm oak [52], conifer wood [53], citrus wood [54] and pine wood [6,[55][56][57].…”
Section: Biochar Feedstocksmentioning
confidence: 99%
“…In addition to production conditions, biochars could be made from varying feedstocks, which would contribute to differences in physical and chemical properties ( Table 1). The feedstocks could be waste materials such as green waste [18], forest waste [46,47], wheat straw [5], sugarcane bagasse [48], rice hull [49], crab shell [50] and Eucalyptus saligna wood chips (byproduct of construction, fuel-wood and pulp wood) [51]. Biochars could also be made from non-waste materials such as holm oak [52], conifer wood [53], citrus wood [54] and pine wood [6,[55][56][57].…”
Section: Biochar Feedstocksmentioning
confidence: 99%
“…Biochar may or may not have phytotoxic effects on plants depending on the original feedstock and process conditions [30]. For instance, the biochar from hardwood, corn and switchgrass under different process conditions had no effect on germination rate [29], while biochar from olive mill waste was phytotoxic [37]. In this study, the germination rates of all basil seeds in the aqueous extracts of biochar-amended mixes were higher than those in DI water, which indicated no phytotoxicity for the biochar used in this study.…”
Section: Media Phytotoxicity and Substrate Propertiesmentioning
confidence: 99%
“…Different kinds of hydrochar have been evaluated as soil conditioners due to some similarities with biochar, such as high carbon content [23][24][25][26][27][28]. Studies showed that the response to application of carbonaceous materials, as hydrochar and biochar, to the soil depends not only on the biomass used in the thermochemical conversion process, but also on the reaction parameters applied [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%